An efficient and green approach for the synthesis of 2, 4-dihydropyrano[2, 3-c]pyrazole-3-carboxylates using Bi2O3/ZrO2 as a reusable catalyst. Issue 29 (3rd May 2018) - Bhaskaruni, Sandeep V. H. S.; Maddila, Suresh; van Zyl, Werner E.; Jonnalagadda, Sreekantha B.
Abstract : Novel bismuth loaded on zirconia (Bi2 O3 /ZrO2 ) as a reusable catalyst to synthesize 2, 4-dihydropyrano[2, 3- c ]pyrazole-3-carboxylates under mild conditions. Abstract : A novel material of bismuth loaded on zirconia (Bi2 O3 /ZrO2 ) is synthesized by simple wet-impregnation method and characterized by several techniques (P-XRD, TEM, SEM, BET, etc. ). Bi2 O3 /ZrO2 proved to be a good catalyst for the four-component, one-pot reaction to produce a new series of 2, 4-dihydropyrano[2, 3- c ]pyrazole-3-carboxylate derivatives with excellent yields (91 to 98%) under mild conditions at RT with short reaction times (≈20 min). The structures of the target molecules were confirmed by 1 H NMR, 13 C NMR, 15 N NMR, HRMS and FT-IR. The catalyst is easily separable and can be reused for six cycles without ostensible loss of activity. This method is inexpensive, atom-efficient and no chromatographic separations are needed.